2022
DOI: 10.3389/fgene.2022.964150
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of 42Sp50 in spotted scat (Scatophagus argus)

Abstract: 42Sp50 is an isoform of the eukaryotic translation elongation factor 1 A (eEF1A) and is vital for fish ovarian development. Spotted scat (Scatophagus argus) is a popular marine cultured fish species in Southern Asia and China, and its artificial reproduction is complicated, with a relatively low success ratio in practice. In this study, the 42Sp50 gene was cloned from spotted scat. Tissue distribution analysis showed that 42Sp50 was mainly expressed in the ovary. qRT-PCR showed that 42Sp50 expression levels gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Our IHC results showed that the location of 42Sp50 in the ovaries of XY-completely sex-reversed individuals was very similar to that in the ovaries of XX females. The location of 42Sp50 in the XY sex-reversed fish obtained by E 2 treatment is also similar to that of the untreated XX females (Figure 5) [17]. Therefore, we speculate that the gonads of XY-completely sex-reversed spotted scat obtained through the preliminary combined treatment trial may have functional ovaries based on the ovarian gene expression profiles.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Our IHC results showed that the location of 42Sp50 in the ovaries of XY-completely sex-reversed individuals was very similar to that in the ovaries of XX females. The location of 42Sp50 in the XY sex-reversed fish obtained by E 2 treatment is also similar to that of the untreated XX females (Figure 5) [17]. Therefore, we speculate that the gonads of XY-completely sex-reversed spotted scat obtained through the preliminary combined treatment trial may have functional ovaries based on the ovarian gene expression profiles.…”
Section: Discussionsupporting
confidence: 62%
“…Genomic DNA (gDNA) was extracted using a DNA extraction kit (AD1173, Guangzhou Aitier Biotechnology Co., Ltd., Guangzhou, China). The gDNA was used to accurately identify the sex of the collected spotted scat using sex identification markers previously obtained in our laboratory [17]. Blood was collected from the caudal vein and kept at 4 • C overnight.…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation